Sejmy Drugiej Rzeczypospolitej - Zakrzewski, Andrzej (Warszawa : Ludowa Spoldzielnia Wydawnicza, 1990)
This is a short history of the various parliaments of the Second Polish Republic, 1918-1945.
Includes bibliographical references.
Keywords: Poland. -- Sejm; Poland -- Politics and government -- 1918-1945.